Technological Processing of Dried Powdered Rosehips to Tablets Through Wet Granulation - Špaglová M.; Matušková M.; Lawson M.K; Čuchorová M.; Čierna M.; Krchňák D.; Mikušová V.; Piešťanský J.; Mikuš P. (Sciendo, 2023)
The pseudo-fruits of Dog Rose are a rich source of L-ascorbic acid and several other active substances, which means their high supportive therapeutic potential. The study aimed to examine the impact of the chosen technological procedure for the preparation of tablets containing rosehip powder on the amount of L-ascorbic acid in the final pharmaceutical form. Drying of the plant drug was performed at room temperature to avoid possible thermal degradation of this heat-sensitive compound. Similarly, drying of the granules after wet granulation in the oven was replaced by natural drying at room temperature. The composition of two types of prepared granule formulations differed in the filler - lactose (LAC) or microcrystalline cellulose (MCC). Apart from the disintegration test, they meet the technological requirements for granules or tablets. Lactose was confirmed as a more suitable filler, which despite the unsuccessful disintegration of the granules, ensures the disintegration of tablets within 15 minutes even without the addition of a special excipient acting as a disintegrant. The content of L-ascorbic acid detected using isotachophoresis - capillary zone electrophoresis was 87.16 ± 5.06 µg in LAC tablets and 63.33 ± 2.83 µg in MCC tablets.